Beaches, Blood, and Ballots : A Black Doctor's Civil Rights Struggle - Mason, Gilbert R. (Book collections on Project MUSE., 2000)
This book, the first to focus on the integration of the Gulf Coast, is Dr. Gilbert R. Mason's eyewitness account of harrowing episodes that occurred there during the civil rights movement. Newly opened by court order, documents from the Mississippi Sovereignty Commission's secret files enhance this riveting memoir written by a major civil rights figure in Mississippi. He joined his friends and allies Aaron Henry and the martyred Medgar Evers to combat injustices in one of the nation's most notorious bastions of segregation. In Mississippi, the civil rights struggle began in May 1959 with "w.